PENGARUH DIMENSI BRAND COMMUNITY TERHADAP PURCHASE INTENTION : Studi Kasus Mi Fans Indonesia - Esih Jayanti; Pranidimas Nino Pratama (JURNAL EKONOMI, 2020)
The object of this research is members of the Mi Fans Indonesia (A case study of the Mi Fans Indonesia). The sample determination uses purposive sampling as many as 79 people. Based on the results of the study it can be concluded that: 1) Consciousness of kind has a significant effect on the purchase intention of the Mi Fans Indonesia. 2) Rituals and traditions have no significant effect on the purchase intention of the Mi Fans Indonesia. 3) Moral responsibility has a significant effect on the purchase intention of the Mi Fans Indonesia. 4) Brand communities have a significant effect on the purchase intention of the Mi Fans Indonesia.The advice to Xiaomi brand is expected to further increase their closeness to the Mi Fans communities at the regional to national level, the Xiaomi brand is expected to further improve product quality and after-sales service to increase community members' trust in the Xiaomi brand, and researchers are expected to be able to search other factors that can affect the purchase intention of the Mi Fans Indonesia. Keywords: Brand community, consciousness of kind, ritual and tradition, moral responsibility, purchase intention.